2023
DOI: 10.1002/brb3.2983
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of urgent inpatient neurologic consultations in a large tertiary hospital center: Follow‐up on the effect of standardized training of residents

Abstract: Background Clinical neurology is difficult for young residents. To familiarize with neurological emergencies as soon as possible for young doctors, the urgent inpatient neurologic consultations were analyzed. Methods A retrospective study was conducted on the urgent inpatient neurologic consultations in a large tertiary hospital for 4 consecutive years. Results A total of 1437 cases were included, and the annual consultation cases gradually decreased from 573 to 257, involving 29 clinical departments. The diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…6,22 In the last study, in which a decrease was observed, the reason for the decrease was attributed to more basic medical information was included in the resident education system. 1 In the present study, together with all of these reasons, we believe that increased defensive medicine is another reason. While the most common reason for consultation was eclampsia, a related disorder to neurology in 2015, we attribute to the same reasons why pre-eclampsia, which is less related to neurology than eclampsia, was the most common reason for consultation in 2022.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…6,22 In the last study, in which a decrease was observed, the reason for the decrease was attributed to more basic medical information was included in the resident education system. 1 In the present study, together with all of these reasons, we believe that increased defensive medicine is another reason. While the most common reason for consultation was eclampsia, a related disorder to neurology in 2015, we attribute to the same reasons why pre-eclampsia, which is less related to neurology than eclampsia, was the most common reason for consultation in 2022.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, urgent inpatient neurological consultations decreased year by year in another study. 1 In the first two studies, an increase in consultations was supposed to be associated with growing diagnostic complexity and specific treatment approaches in neurology. 6,22 In the last study, in which a decrease was observed, the reason for the decrease was attributed to more basic medical information was included in the resident education system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation